1인 뷰티샵의 브랜드 개성과 브랜드 효익이 고객 충성도에 미치는 영향 - 이서현; Seo-hyun Lee; 허혜순; Hye-soon Heo; 우미옥; Mi-ock Woo (한국미용학회지, 2024)
The purpose of this study was to examine the impact of a personal beauty shop’s brand personality and brand benefit on customer loyalty, and a frequency analysis of the demographic characteristics was conducted using the SPSS 26.0 statistical program. The reliability and validity of brand personality, brand benefit and customer loyalty were analyzed, and to examine the influential relation between variables, a multiple regression analysis was conducted. Based on the study results, regarding the impact of a personal beauty shop’s brand personality and brand benefit on customer loyalty, it was confirmed that there was a significant impact among first, practical/modern factors serving as the sub-factors of brand personality, second, functional/emotional factors serving as the sub-factors of brand benefit, and third, customer loyalty. Therefore, it is thought that branding effects capable of enhancing a beauty shop’s brand personality is important.